A physical activity focused typology to guide urban neighbourhood evaluation and re‐design: Evidence from Ankara, Türkiye - Ozuduru, Burcu Halide; Gurel, Zeynep Asli; Yigiter, Ayten (Geographical research, 2025)
Physical inactivity is a major risk for non‐communicable diseases (NCDs) and is a growing public health epidemic of the 21st century. Limited walkability, a lack of green spaces in dense neighbourhoods, and excessive reliance on motorised transportation support sedentary lifestyles. Urban planning and design decisions shape these built environments by encouraging or restricting physical activity (PA). This study uses applied geographical analysis, including spatial network analytics, principal component analysis (PCA), indexing, and clustering, performed with the k ‐means elbow method to define neighbourhood typologies for planning healthy cities that support PA. We aggregate individual‐level data to inform policies that target neighbourhoods for walkability and other healthy city interventions. We demonstrate this in the context of Türkiye’s capital city, Ankara, which is subject to car‐driven urban sprawl with low‐density peripheral development. Our findings show that the features that support PA are associated with housing density, accessibility (betweenness), centrality, and local health infrastructure. These are most commonly found in inner‐city mature neighbourhoods in Ankara, which aligns with Ankara’s earlier master plans. The study, stemming from time geography of health, presents a typological guide using an applied geographical method and highlights that designing connected, walkable, and mixed‐use developments can reduce physical inactivity and create healthier cities around the world.